2020
DOI: 10.32635/2176-9745.rbc.2019v65n4.400
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de Nanopartículas no Tratamento do Câncer: Aspectos Gerais, Mecanismos de Ação Antineoplásicos e Aplicabilidades Tumorais

Abstract: Introdução: Os avanços tecnológicos das últimas décadas levaram ao desenvolvimento de abordagens terapêuticas na medicina em uma nova escala de aplicações moleculares nanométricas, permitindo o estabelecimento de novas terapias como a nanoterapia. O uso de nanopartículas implica inúmeras oportunidades e também grandes desafios para a aplicação humana, esse uso requer uma compreensão minunciosa da biocompatibilidade e da farmacodinâmica das moléculas. No câncer, as nanopartículas atuam principalmente na forma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
(92 reference statements)
0
0
0
Order By: Relevance
“…In terms of therapeutic effectiveness, researchers have observed that nanoparticles exhibit optimal internalization by cancer cells, especially in the treatment of diseases like breast cancer [27]. Their enhanced permeation into the target cells not only improves drug delivery, but also renders the nanoformulation more cytotoxic when compared to free drugs [28].…”
Section: Nanoformulationmentioning
confidence: 99%
“…In terms of therapeutic effectiveness, researchers have observed that nanoparticles exhibit optimal internalization by cancer cells, especially in the treatment of diseases like breast cancer [27]. Their enhanced permeation into the target cells not only improves drug delivery, but also renders the nanoformulation more cytotoxic when compared to free drugs [28].…”
Section: Nanoformulationmentioning
confidence: 99%